2014
DOI: 10.1007/s10565-014-9276-3
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of sestrin-2 expression protects against endothelial toxicity of angiotensin II

Abstract: Sestrin-2 (SESN2) is involved in the cellular response to different stress conditions. However, the function of SESN2 in the cardiovascular system remains unknown. In the present study, we tested whether SESN2 has a beneficial effect on vascular endothelial damage induced by angiotensin II (AngII). Firstly, we found that AngII induces expression of SESN2 in human umbilical vein endothelial cells (HUVECs) in a time-dependent and dose-dependent manner. We also found that knockdown of SESN2 using small RNA interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…In human umbilical vein endothelial cells, the expression of Sesn2 was induced after AngII stimulation with a time-dependent and dose-dependent manner. Also, knockdown of Sesn2 using small RNA interference promoted cellular toxicity of AngII, as demonstrated by the reduced cell viability, exacerbated oxidative stress, and increased apoptosis [21]. …”
Section: Sesns In Heartmentioning
confidence: 99%
“…In human umbilical vein endothelial cells, the expression of Sesn2 was induced after AngII stimulation with a time-dependent and dose-dependent manner. Also, knockdown of Sesn2 using small RNA interference promoted cellular toxicity of AngII, as demonstrated by the reduced cell viability, exacerbated oxidative stress, and increased apoptosis [21]. …”
Section: Sesns In Heartmentioning
confidence: 99%
“…In hypoxic-ischemic encephalopathy, Sestrin 2 has been shown to reverse neurological dysfunction and provide a neuroprotective effect [18]. Additional evidence has indicated that Sestrin 2 upregulation protects against angiotensin II-induced endothelial dysfunction [19]. Our results unveiled that administration of Sestrin 2 ameliorates liver fibrosis in vivo.…”
Section: Discussionmentioning
confidence: 55%
“…Fhit (fragile histidine triad gene transcript) whose protein promotes apoptosis and suppresses cell proliferation (Huang et al , 2014); and 4. Ace (angiotensin converting enzyme transcript), an enzyme which converts angiotensin I to the physiologic active peptide angiotensin II, a proapoptotic protein (Wang et al , 2015, Yi et al , 2014). Two other transcripts downregulated were Ermn whose protein is an oligodendrocyte-specific protein surrounding myelin axons necessary for action potentials (Brockschnieder et al , 2006) and Nrgn involved in promoting synaptic transmission (Zhong et al , 2009).…”
Section: Discussionmentioning
confidence: 99%